An Analysis Of Corruption in Multi-Party Politics, Government Legitimacy, and Manifestations Of Democracy in Nigeria From 1999 to 2023 - Abalaka, J.N; Ajiteru, S.A.R; Sulaiman, T.H (International Journal of Humanities and Social Sciences Reviews, 2025)
This study examines the impact of political and public official corruption on Nigerian democracy and government legitimacy between 1999 and 2023. The research uses a qualitative descriptive approach, supported by documentary analysis, with the elite theory framework as the basis for gathering and evaluating relevant data. The study argues that the pervasive corruption within Nigeria’s democratic system is largely driven by the ruling elites, who control both political power and wealth. The elites are able to appropriate state powers and utilize them to amass resources and build networks of patronage, which are crucial for maintaining their dominance and subjugating the un-elite majority. Through the lens of power relations, the study highlights how these corrupt practices have led to the entrenchment of the elites’ control over political and economic systems. The study concludes that political corruption has significantly undermined the government's ability to provide essential public goods and services, which has, in turn, contributed to a decline in public trust in Nigeria's political institutions and democratic processes during this period. As the political landscape has become increasingly dominated by corruption, citizens have grown disillusioned with the system. The study recommends that Nigeria's political leadership reassess its current, money-driven and self-serving political approach, and adopt a more service-oriented model. Strengthening the rule of law, promoting public involvement in governance, and ensuring governmental accountability and legitimacy could help prevent Nigeria's slide toward political authoritarianism and reverse the democratic decline.